Gender equality norms across generations: Evidence from a representative sample - Francesca Barigozzi; Caterina Gaggini; Natalia Montinari (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2024)
Using a representative survey of the Italian population (N=1,501), we elicit gender norms regarding the sharing of domestic chores within couples, employing the methodology of Krupka and Weber (2013). Two vignettes present hypothetical scenarios in which the partners' labor supply, chore allocations, and the gender of the partner proposing a specific chore allocation vary. Participants are asked to rate the social appropriateness of different chore allocations across scenarios that combine these dimensions. We find evidence of a framing effect and a gender double standard among the middle and older generations, but not among the younger generation, in which we observe a decline in adherence to the 'male breadwinner' model. These findings suggest that the younger generation is endorsing a more progressive gender norms. We also show that perceived social norms display a significant association with women's labor market outcomes based on administrative data at the regional level.
Keywords: A13; C90; D01; J16; 330; social norms; gender norms; representative surveys; framing effects; double standards